2020
DOI: 10.1039/c9ta11934e
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of polypyrrole tubes using curcumin template for excellent electrochemical performance in supercapacitors

Abstract: In this study, polypyrrole (PPy) having a unique hollow tubular structure was prepared through a simple and scalable one-step method of in situ chemical oxidative polymerization, employing curcumin, a plant-derived material, as a readily removable and eco-friendly template.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…Nano-micro structuring can lead to effective charge transport and better electrolyte exposure. A scalable eco-friendly method to achieve the cyclic stability by accommodating the morphological swelling shrinking process remains appealing [102].…”
Section: Polypyrrole Sensorsmentioning
confidence: 99%
“…Nano-micro structuring can lead to effective charge transport and better electrolyte exposure. A scalable eco-friendly method to achieve the cyclic stability by accommodating the morphological swelling shrinking process remains appealing [102].…”
Section: Polypyrrole Sensorsmentioning
confidence: 99%
“…Dubal et al [ 47 ] observed that multilayer PPy nanosheets exhibited a specific capacitance of 586 F·g −1 at a scan rate of 2 mV·s −1 , with a Brunauer–Emmett–Teller (BET) surface area of 37.1 m 2 ·g −1 , which is higher than that of PPy nanoribbons and nanobricks. Jyothibasu et al [ 48 ] prepared PPy tubes using one-step in situ chemical oxidative polymerization with curcumin as a template, which was combined with functionalized carbon nanotubes (f-CNTs) as electrode materials. The electrodes exhibited morphological uniformity, a favorable hierarchical porous structure, a large surface area, and excellent electrochemical properties, including outstanding cycling stability (retention of 118.18% of the initial capacitance after 12,500 charge/discharge cycles).…”
Section: Electrode Materialsmentioning
confidence: 99%
“…Equations ( 4), ( 5), ( 6), and (7) were used to determine the areal capacitance (Ccell, F cm -2 ), energy density (E, µW h cm -2 ), power density (P, µW cm -2 ), and volumetric capacitance (Cv-cell, F cm -3 ), respectively, of the asymmetric supercapacitor (Jyothibasu and Lee 2020).…”
Section: Ccm//ccf Asymmetric Supercapacitorsmentioning
confidence: 99%